Evaluation of a school based comprehensive sexuality education program among very young adolescents in rural Uganda - Kemigisha, Elizabeth; Bruce, Katharine; Ivanova, Olena; Leye, Els; Coene, Gily; Ruzaaza, Gad N.; Ninsiima, Anna B.; Mlahagwa, Wendo; Nyakato, Viola N.; Michielsen, Kristien (BMC Public Health, 2019)
Limited research has been conducted on the effectiveness of sexuality education for very young adolescents (VYAs) ages 10–14 years in Sub-Saharan Africa. Furthermore, evaluations of sexuality education programs often report outcomes of risky sexual practices, yet positive aspects of sexuality are hardly studied and rarely reported. This study evaluates the effectiveness of a Comprehensive Sexuality Education (CSE) intervention for VYAs in Uganda, analyzing both positive and negative outcome indicators. Methods: We conducted a mixed methods study, incorporating a cluster randomized trial (NCT03669913) among pupils in 33 randomly selected primary schools in Mbarara district. This was followed by a qualitative evaluation of the intervention in 4 schools that included 14 in-depth interviews and 3 focus group discussions distributed among pupils, teachers and parents. Quantitative data were analyzed using ordered logistic regression to compare differences in the change from baseline to endline between the intervention and control arms. We conducted bivariate analysis and multiple regression analysis controlling for key covariates, including age, gender, school location (rural vs urban), truancy, and orphanhood. Qualitative data were analyzed by thematic approach using ATLAS TI. Results: Between July 2016 and August 2017, 1096 pupils were recruited. Outcomes were studied among 380 pupils in the intervention arm and 484 pupils in the control arm. The proportion of pupils who ever had sex increased from 9 to 12.1% in intervention compared to 5.2 to 7.4% in the control group between baseline and endline, however the differences between groups were not statistically significant. We found greater improvements in sexual and reproductive health (SRH) knowledge among intervention schools (AOR: 2.18, 95% CI: 1.66–2.86) and no significant differences in self-esteem, body image or gender equitable norms. Qualitative evidence echoes perceived SRH knowledge acquisition, increased their perception of SRH related risks, and intentions to delay sexual intercourse to prevent unwanted pregnancy, HIV and other STIs.
Keywords: Comprehensive sexuality education; Sexual and reproductive health; Evaluation